Advances in Urology: A Comprehensive Literature Review on Urolithiasis Management and Innovations - Ramadhan, Reza Dwi; Wijaya, Mangkubumi Putra; Hidayat, Dzaky Ramadhan (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2025)
Introduction. Urolithiasis is a prevalent condition, affecting approximately 12% of the global population at some point in their lives, with higher incidence rates reported in industrialized nations. This condition poses significant health challenges worldwide due to its recurrence and the associated healthcare burden. Recent innovations in imaging, minimally invasive techniques, and pharmacotherapy have revolutionized the field. This review aims to explore recent updates and innovations in the management of urolithiasis, from diagnosis to therapy. Methods. A systematic search using predefined keywords in multiple databases was done. Peer-reviewed articles, clinical trials, meta-analyses, and systematic reviews focused on urolithiasis management, diagnostic techniques, therapeutic innovations, and preventive strategies were analyzed. Articles from January 2015—December 2023 were included, reviewed for its eligibility, and extracted. Results. Emerging pharmacological agents (eg. empagliflozin, thiosulfate) offer new avenues for prevention and recurrence reduction, particularly for patients with recurrent urolithiasis, although not as primary therapy. Additionally, the integration of artificial intelligence and machine learning is beginning to play a role in predicting stone recurrence and optimizing treatment plans. Conclusion. This review highlights the importance of a personalized, patient-centered approach in managing urolithiasis, emphasizing the need for ongoing research and clinical trials to further refine these innovations. Keywords: artificial intelligence, disease management, urinary stone disease, urolithiasis